Advances in Pathogenesis and Therapy of Hemolytic Uremic Syndrome Caused by Shiga Toxin-2 - Ibarra, Cristina Adriana (2013)
Shiga toxin (Stx) producing Escherichia coli (STEC) is responsible to bloody diarrhea (hemorrhagic colitis) and the hemolytic uremic syndrome (HUS). STEC strains carry inducible lambda phages integrated into their genomes that encode Stx 1 and=or 2, with several allelic variants each one. O157:H7 is the serotype that was documented in the vast majority of HUS cases although non-O157 serotypes have been increasingly reported to account for HUS cases. However, the outbreak that occurred in central Europe during late spring of 2011 showed that the pathogen was E. coli O104:H4. More than 4,000 persons were infected mainly in Germany, and it produced more than 900 cases of HUS resulting in 54 deaths. E. coli O104:H4 is a hybrid organism that combines some of the virulence genes of STEC and enteroaggregative E. coli specially production of Stx2 and the adherence mechanisms to intestinal epithelium. The differences in the epidemiology and presentation of E. coli pathogen meant a challenge for public health and scientific research to increase the knowledge of HUS-pathophysiology and to improve available therapies to treat HUS.